Analisis Penerapan Manajemen Agile Pada PT Telekomunikasi Indonesia Divisi Digital Service - Azkaa Agdaviswan; Agdaviswan, Pudji Muljono; Agdaviswan, Joko Purwono (Institut Pertanian Bogor, 2021)
PT Telekomunikasi Indonesia is a state-owned enterprise which specializing in telecommunication and information technology. This research purpose is to identify which factors that influenced in the management method application process in post-transition from traditional management method (Waterfall) and after agile management method. Sample in this research came from PT Telekomunikasi Indonesia Digital Service Division with job position ranged from Officer 2 and the sampling using the questionnaire which validated with Kendall’s W and with amount of the respondent is 19 respondents. The analysis method is using Fuzzy-Analytic Hierarchy Process (F-AHP) and the validation is using MATLAB. The research is using category criteria which are Human Resourcing (HR), coordination, technology, project management and software methodology. Next step analyzing every category with their influenced factors. The result is showing that Human Resourcing (HR) become the most influenced category in every management method application, traditional management method (Waterfall) or agile management method.